Pan American Arctic survey flight: Greenland to Iceland transatlantic route, Charles A. Lindbergh, 1933 - Pan American World Airways, Inc. (1933)
Includes photographs. Some materials in this folder were not scanned, but are available for viewing at the University of Miami Libraries Special Collections. This item was digitized as part of the "Digitizing the 'World's Most Experienced Airline'" project, supported by a grant from the Council on Library and Information Resources (CLIR). The grant program is made possible by funding from The Andrew W. Mellon Foundation.